Redox active nitrogen-containing conjugated porous polymer: An organic heterogeneous electrocatalysts for oxygen reduction reaction. (November 2019) - Bandyopadhyay, Sujoy; Boukhvalov, Danil W.; Nayak, Arpan Kumar; Ha, Su Ryong; Shin, Hee Jeong; Kwon, Jiseok; Song, Taeseup; Choi, Hyosung
Abstract: Here we report the fabrication of a novel three-dimensional conjugated porous polymer (CPP–P1) developed by a palladium-catalysed Sonogashira poly-condensation reaction. The solid polymer was thoroughly characterized by 13 C cross-polarization solid-state NMR and X-ray photoelectron spectroscopy (XPS). The pristine nitrogen-containing CPP was explored as an electrocatalyst for the oxygen reduction reaction (ORR) in alkaline media 0.1 M KOH. We observed that in the case of pristine polymer CPP-P1 oxygen reduction occurs through four electron transfer pathway with excellent stability and good tolerance to methanol. The detailed molecular-level structure for oxygen reduction and mode of oxygen binding site to the polymer was explained by density functional theory (DFT) calculation. Highlights: The conjugated microporous polymer, CPP-P1, has explored metal-free electrocatalysis for oxygen reduction reaction that exhibit the onset potential 0.87 V with a high current density of 4.71 mA cm −2 . CPP-P1 has good tolerance to methanol. We explore the detailed molecular level picture for oxygen reduction reaction by DFT investigation.